Effects of temperature anneal cycling on a cryogenically proton irradiated CCD. (8th November 2021) - Parsons, S.; Buggey, T.; Holland, A.; Sembay, S.; Randall, G.; Hetherington, O.; Yeoman, D.; Hall, D.; Verhoeve, P.; Soman, M.
Abstract: Throughout a typical Earth orbit a satellite is constantly bombarded by radiation with trapped and solar protons being of particular concern as they gradually damage the focal plane devices throughout the mission and degrade their performance. To understand the impact the damage has on CCDs and how it varies with their thermal history a proton radiation campaign has been carried out using a CCD280. The CCD is irradiated at 153 K and gradually warmed to 188 K in 5 K increments with Fe 55 X-ray, dark current and trap pumping images taken at 153 K after each anneal step. The results show that despite the trap landscape changing throughout the anneal it has little impact on parallel charge transfer inefficiency. This is thought to be because most traps are unaffected and a lot of those that do anneal only move from the continuum between distinct trap species and into a nearby divacancy trap "peak" whose emission time constant is similar enough to still impact the CTI. In terms of using a CCD280 or similar devices in a mission the CTI being unaffected by thermal annealing up to 188 K means that any CTI correction needed as the radiation damage builds up does not have to take into account the thermal history of the focal plane. However, it is possible that a significant amount of annealing will occur at temperatures greater than 188 K and care should be taken when a mission is operating in this range to gather accurate pre-flight data.